2018
DOI: 10.14715/cmb/2018.64.11.13
|View full text |Cite
|
Sign up to set email alerts
|

The effects of apelin on myometrium contractions in pregnant rats

Abstract: Apelin, which is a new hormone, is secreted especially in the brain by hypothalamus as well as by many other organs like the stomach, fat tissue, and the heart. For apelin, whose possible effects on many bodily functions like the endocrine system, cardiovascular system and metabolic activities are still under investigation, the reproductive system is also an important target area. The purpose of the present study was to investigate the effects of plasma apelin levels in rats that were in diestrus, pregnancy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…In humans, an in vitro study brought evidence that apelin had inhibitory effects on uterine contractility by down-regulating spontaneous and oxytocin-induced contractions in the human myometrium [149]. Similar results have since been found in rats [150].…”
Section: Adipokines and Pregnancymentioning
confidence: 64%
“…In humans, an in vitro study brought evidence that apelin had inhibitory effects on uterine contractility by down-regulating spontaneous and oxytocin-induced contractions in the human myometrium [149]. Similar results have since been found in rats [150].…”
Section: Adipokines and Pregnancymentioning
confidence: 64%
“…However, at variance with those of Kacar et al [6] who observed that addition of apelin to organ bath fluid containing strips isolated from pregnant rat uterus at day 21 produced a significant increase in both frequency and amplitude of uterine contraction and showed that this effect occurred in Ca 2+ free medium and did not occur in presence of protein kinase C inhibitor suggesting that PKC pathway but not extracellular Ca 2+ might play a role in these mechanism. They postulated that apelin might be an endogenous peptide that play a role on uterine contraction at birth in rats facilitating parturition.…”
Section: Discussionmentioning
confidence: 55%
“…There are contradictory reports about the effect of apelin on uterine contractility Hehir & Morrison [5] observed that apelin exerts an inhibitory effect on human myometrial contractility in vitro, in tissue obtained during pregnancy. In contrast, Kacar et al [6] reported that apelin induces myometrial contractions.…”
Section: Introductionmentioning
confidence: 90%
“…An in vitro study showed that APLN played a vasodilation role in suppressing both spontaneous and oxytocin-induced contraction in human myometrial fibers (Hehir & Morrison, 2012). However, serum APLN was also reported to exert a positive inotropic effect in rat myometrial layer via PKC-mediated intracellular Ca 2+ amplication (Kacar et al, 2018). These opposite results may be explained by the intracellular balance between vascular dilation and smooth muscle contraction mechanisms of apelinergic system, as well as the impacts of species diversity and reagent concentrations.…”
Section: Role Of Apln In Uterus 61 Distribution and Function Of Aplnmentioning
confidence: 99%